LKS DAN MODEL COOPERATIF LEARNING (Salah Satu Alternatif Mengefisienkan Waktu pada KTSP) - Tayeb, Thamrin (Universitas Islam Negeri Alauddin Makassar, 2016)
Education Unit Level Curriculum or Kurikulum Tingkat Satuan Pendidikan (KTSP) is a curriculum that almost deals with competency-based curriculum. KTSP is loaded with various kinds of administration and the possibilities if it is implemented by teachers. It spends about 8-9 hours for a week. Meanwhile, the average time set by the educational unit in the classroom, for example, mathematics subjects fo class X, XI, and XII, is only 4 hours per a week. So, how can a teacher be able to implement the curriculum in schools. Therefore, the author offers students worksheets and Cooperative Learning model as the solutions for time efficiency in implementing the curriculum in the Educational Unit. Students’ worksheet is a sheet that contains guidelines for students to doing planned activities systematically, rather than just solving problems. While cooperative learning model is learning that emphasizes the students work collaboratively associated with the work of the group consisting of 4-5 students. The goal is that the group provides the opportunity for students to engage actively in thinking and learning process.